A communication from the Hon. Henry A. Wise - Wise, Henry A. (Henry Alexander), 1806-1876 (House document (Virginia. General Assembly. House of Delegates), 1836)
March 15, 1836 Communication from U.S. Representative Henry A. Wise regarding the Virginia legislature's resolution which would prevent the U.S. Congress from abolishing slavery in the District of Columbia and territories. Wise recounted why he was unable to so present these resolutions.